2012
DOI: 10.3390/nu4060436
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Phosphate Nutrition Alters in Vivo and in Vitro Satellite Cell Activity in Pigs

Abstract: Satellite cell activity is necessary for postnatal skeletal muscle growth. Severe phosphate (PO4) deficiency can alter satellite cell activity, however the role of neonatal PO4 nutrition on satellite cell biology remains obscure. Twenty-one piglets (1 day of age, 1.8 ± 0.2 kg BW) were pair-fed liquid diets that were either PO4 adequate (0.9% total P), supra-adequate (1.2% total P) in PO4 requirement or deficient (0.7% total P) in PO4 content for 12 days. Body weight was recorded daily and blood samples collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, the gene expression of HAMP calculated with reference to CB-G4 shows a progressively decreasing trend, starting from the group of anemic piglets fed bread with microencapsulated iron (FeMB-G1), followed by the group given non-encapsulated iron bread FeSB-G2 and finally the anemic group, CB-G3, which was fed with control bread (Figure 1A). This trend, showing a slight up-regulation in groups with iron fortified bread in respect to the anemic group, can be explained by the fact that iron is the most important proven biological factor for inducing hepcidin expression, while there is also evidence that both iron saturation of plasma and hepatic iron loading stimulate hepcidin synthesis [25,29]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the gene expression of HAMP calculated with reference to CB-G4 shows a progressively decreasing trend, starting from the group of anemic piglets fed bread with microencapsulated iron (FeMB-G1), followed by the group given non-encapsulated iron bread FeSB-G2 and finally the anemic group, CB-G3, which was fed with control bread (Figure 1A). This trend, showing a slight up-regulation in groups with iron fortified bread in respect to the anemic group, can be explained by the fact that iron is the most important proven biological factor for inducing hepcidin expression, while there is also evidence that both iron saturation of plasma and hepatic iron loading stimulate hepcidin synthesis [25,29]. …”
Section: Resultsmentioning
confidence: 99%
“…However, further improvements are needed as a result of constantly increased growth performance following contemporary breeding management, disease control, advances in physiology, and selection programs ( 14 , 65 ). Indeed, genetics potentially has an impact on P utilization in pigs ( 2 , 4 , 30 ).…”
mentioning
confidence: 99%
“…Moreover, differentiation assays confirmed their ability to differentiate into the myogenic lineage. In several studies, Desmin rather than MyoG has been used to analyze the purity of SC isolates from piglet muscles [ 23 , 54 , 55 ]. Although the proportion of Desmin+ cells significantly increased from an average of 25% to 63% during culture in our study, it was clearly below the values observed for MyoG.…”
Section: Discussionmentioning
confidence: 99%